The effects of reservoir geometry on the seismic response of gravity dams. - Millán, M. A.
Conventional seismic analysis of gravity dams assumes that the behaviour of the dam?water?soil system can be represented using a 2-D model since dam vertical contraction joints between blocks allow them to vibrate independently from each other. The 2-D model assumes the reservoir to be infinite and of constant width, which is not true for certain types of reservoirs. In this paper, a boundary element method (BEM) model in the frequency domain is used to investigate the influence of the reservoir geometry on the hydrodynamic dam response. Important conceptual conclusions about the dam?reservoir system behaviour are obtained using this model. The results show that the reservoir shape influences the seismic response of the dam, making it necessary to account for 3-D effects in order to obtain accurate results. In particular, the 3-D pressure and displacement responses can be substantially larger than those computed with the 2-D model.
Keywords: Seismic analysis; Dams; Hydrodynamic pressures; Fluid?structure interaction; Structural dynamics